2015
DOI: 10.5901/mjss.2015.v6n1s3p475
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Strategy: Problems and Solutions

Abstract: The paper deals with the implementation of the strategy as a key element of the strategic process. Developed organizational and management mechanism of the process of implementation of the strategy involves the exercise of choice of methods and resources management in accordance with the nature of the factors of internal processes (capacity) of the enterprise and the external environment in which it operates, and to exercise control on the basis of information on the implementation of the organization's proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The analysis of papers in this subject area has shown the interest of the scientific community in the study of personal risks of interested parties in products in order to anticipate their expectations and ensure the competitiveness of the enterprise [2][3][4][5][6][7][8][9][10]. In this regard, it may be promising to study the personal risks of consumers, which are considered within this study as problems, threats, errors, damage, etc., i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of papers in this subject area has shown the interest of the scientific community in the study of personal risks of interested parties in products in order to anticipate their expectations and ensure the competitiveness of the enterprise [2][3][4][5][6][7][8][9][10]. In this regard, it may be promising to study the personal risks of consumers, which are considered within this study as problems, threats, errors, damage, etc., i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Scientific studies of the nature of consumer requirements for products have revealed their heterogeneity and differentiation [1,2]. At the same time, risk-based approach in accordance with international standards ISO 9000:2015 provides that ensuring and anticipating consumer expectations from products of an enterprise means the study of personal risks of interested parties, which reduces the level of uncertainty in understanding the degree of the product value from the consumer's point of view.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed comparison of the Russian project goals and the goals of foreign campaigns shows the difference in approaches: foreign campaigns are created to satisfy citizens' needs through modernization of authorities/bodies with the introduction of improved ICT; the Russian approach is directed to modernization of governmental bodies through the introduction of ICT [8]. That is, the means used in foreign strategies as the instruments are accepted as the anticipated result in the Russian policy [9].…”
Section: Research Questionsmentioning
confidence: 99%
“…Asaul (Asaul and Batrac, 2001), Ying Xie (Xie, 2011), Rumaizah Mohd Nordin (Rumaizah et al, 2012) and others (Khasanov, 2014). At the same time, in the conditions of modern realities strategy development and implementation of regional housing policy is still in the early stages of its development and does not have the support, based on an understanding of the population of the importance of this strategy for the improvement of living standards (Yashin et al, 2015;Assanova, 2015).…”
Section: Latest Research and Publications Analysismentioning
confidence: 99%